New genera and species of deep-sea Goniasteridae (Asteroidea) from the North Pacific - Mah, Christopher L. (Zootaxa, 2024)
The North Pacific is a vast region, and undiscovered taxa from deep-sea habitats (>200 m), especially from below 1000 m continue to be described based on in situ and museum collections. The Goniasteridae is the most diverse of Asteroidea and further discoveries continue to be made. Here, one new genus and seven new species are described and novel occurrences recorded. In situ observations from R/V Nautilus and MBARI permit further insight into goniasterid ecology and morphology in deep-sea settings.